2011
DOI: 10.1016/j.juro.2011.03.131
|View full text |Cite
|
Sign up to set email alerts
|

Mid-Term Complications After Placement of the Male Adjustable Suburethral Sling: A Single Center Experience

Abstract: In our study cohort the Argus suburethral sling was associated with serious mechanical and infectious complications, and sparse functional results with negative impact on patient quality of life. Based on the results of this study significant changes are warranted in the sling system and in the implantation technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
1
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 24 publications
1
31
1
3
Order By: Relevance
“…Dalpiaz et al [17] studied potential risk factors for general complication rates after Argus classic implantation and found no statistically significant impact of median age, comorbidity, incontinence grade, or previous pelvic irradiation. In contrast, Bochove-Overgaauw and Schrier [13] observed increased complication rates after Argus classic implantation in previously irradiated patients and patients with a history of urethral stricture disease.…”
Section: Discussionmentioning
confidence: 99%
“…Dalpiaz et al [17] studied potential risk factors for general complication rates after Argus classic implantation and found no statistically significant impact of median age, comorbidity, incontinence grade, or previous pelvic irradiation. In contrast, Bochove-Overgaauw and Schrier [13] observed increased complication rates after Argus classic implantation in previously irradiated patients and patients with a history of urethral stricture disease.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4][5][6][7]12 Reported continence rate for the ARGUS Classic is 17%-79% in a maximum follow-up of up to 45 months. In general, onethird of the patients need readjustments.…”
Section: Complicationsmentioning
confidence: 99%
“…Mean number of adjustments were 3.97 (0-9) resp. 3.8 (1)(2)(3)(4)(5)(6). No intraoperative complications are reported.…”
Section: Complicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In that study, 79.2% of patients were considered to be dry, and the incontinence quality of life scale improved from a mean of 28.8 to 63.2 points after Argus sling placement. Dalpiaz et al [70] reported mid-term complications after the placement of the Argus sling at a median follow-up of 35 months. Overall, 24 patients (83%) experienced complications, including acute urinary retention (35%) and removal of the sling (35%) owing to urethral erosion, infection, system dislocation, urinary retention, and persistent pain.…”
Section: Management Of Stress Incontinencementioning
confidence: 99%